Crush syndrome [Crush sendromu] - (:unkn) unknown (My University, 2002)
Crush syndrome is the systemic manifestation of muscle injury caused by prolonged limb compression sustained in crush injury. It is characterized by hypovolemic shock, hyperkalemia, acute renal failure and muscule necrosis. Crush syndrome is typically encountered in wars, in earthquakes, in industrial and traffic accident. It was first descripted by Bywaters and Beal in bombing raids of London Blitz during World War II. The muscules contain the largest pool of body water, potassium and other solutes. Therefore muscule injuries may unleash extreme disturbances in plasma electrolyte concentration and body fluid compartments. Victims with massive muscule crushing, as is classically observed after earthquakes, suffer from profound hypovolemic shock. Therefore, the mainstay of management of these casualties is early massive volume replacement started preferably in the field. Mannitol and forse diuresis with the alkanization of urine are the preferred treatment for the prevention of acute renal failure (ARF). Established ARF fully recovers even after prolonged dialysis treatment.